Learning from Everyone - David Bleich (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
In the teaching of writing and literature, it would be helpful to teachers and students to encourage students to overtake, use, and reuse one another's various uses of language in essays and other course work. This essay was the keynote address at the Fourth Annual Colorado Conference of the Assembly for Expanded Perspectives on Learning in Estes Park, Colorado in June 1998.